Nematic colloidal assemblies: Towards photonic crystals and metamaterials - Žumer, S; Muševič, I; Ravnik, M; Škarabot, M; Poberaj, I; Babič, D; Tkalec, U (2008)
Colloidal structures assembled in confined nematic liquid crystals are examined. Theoretical predictions based on Landau-type approaches are complemented with the latest studies of laser assisted colloidal assembling. Effective colloidal interactions are particularly sensitive to the confinement and external fields. Their complexity leads to numerous stable or metastable colloidal superstructures not present in isotropic solvents. Particularly important are colloidal structures coupled by entangled disclinations. Such a string-like coupling is very robust and opens new routes to assemble new photonic materials.